Analisis Pengaruh Penambahan Bilge Keel Terhadap Gerak Rolling pada Kapal Pandu IPCM Menggunakan Metode Strip-Theory - Amjad Mulkus Fadlurrohman (Fakultas Teknik, 2023)
A pilot boat served the purpose of guiding other ships to safely dock at the harbor. The motion of the ship determined the voyage of the pilot boat. The chine on a ship was utilized to mitigate roll motion. Imperfections in ship design need the addition of a bilge keel installed on the chine of the IPCM pilot boat to the further dampen roll motion. The research used strip theory method via maxsurf motion, a commonly used approach in seakeeping testing due to its ability to calculate 2D models from 3D models. According to the research, the addition of bilge keels to IPCM pilot boats, tested without bilge keels from model 1 to model 12 on irregular waves with wave heights ranging from 0.65 m to 4.2 m and wave directions of 45˚, 90˚, 135˚ at speeds of 15 knots and 20 knots, had a significant effect. Roll motion could be reduced up to 13.44% after adding a bilge keel in model 11, identified as the most effective in mitigating roll motion. The increase in tilge resistance was a direct effect of the bilge keel addition. Model 3 was identified as the superior model among all, with only a 1.15% difference compared to conditions without an additional bilge keel. Although model 11 demonstrated superior performance in dampering roll motion compared to model 3, durability difference was only 3.40%, making model 11 as the optimal choice.
Entry oleh Arif 2026 Februari 06
Keywords: Pilot Boat; Bilge Keel; Roll Motion